Impregnation Of Mwcnt Zno Dual Nanofiller Mixed Matrix Membrane - Pang, Wen Yu (2020)
Membrane filtration for humic acid removal faced challenges in term of fouling caused by solute itself and the bacteria found in the feed stream. There were a lot of studies showed great antifouling and antibacterial properties at the same time. Hence, dual nanofiller polyethersulfone (PES) membrane was synthesized via phase inversion method by blending different ratio zinc oxide (ZnO) and multiwalled carbon nanotube (MWCNT) into PES dope solution. Prior blending, MWCNT was functionalized using nitric acid to form hydrophilic hydroxyl and carboxylic group on the tube surface for dispersion. The combination of both MWCNT and ZnO was able to produce combined effect improved antifouling and antibacterial synergistic effect that does not require additional reaction or interaction between them. The synergistic effect of both nanofiller on the membrane properties was characterized in term of dope solution viscosity, morphology, surface roughness, membrane pore size and porosity, hydrophilicity, thermal stability and filtration performance. The results reveal that the membrane containing dual nanofiller was porous compared to single filler membrane and neat PES membrane. Furthermore, the increase of FCNT ratio caused the membrane hydrophilicity increased. The addition of both nanofiller was found to increase the dope solution viscosity and reduced the surface roughness of the membrane. As FCNT ratio in the membrane increased, higher permeate flux was recorded. When the nanofiller of the membrane was dominated by FCNT (i.e., ratio more than 0.5), the humic acid (HA) rejection was not affected much even though pore size of the membrane was increased. It was also been found that without photocatalytic reaction, the antibacterial properties contributed by ZnO was antiadhesion effect rather than inhibition of the bacteria. Out of all the fabricated membranes, FZ3 (dual nanofiller membrane produced with 1wt% of equal ratio functionalized MWCNT and ZnO mixture) was able to achieve optimum performance with pure water flux of 89.66 L/m2.h and HA rejection of 93.21%. Judging from its lower fouling resistance and less bacterial adhesion onto the membrane surface, FZ3 was the most antifouling and antibacterial dual nanofiller membrane.